A Pre-Experimental Study to Assess the Effectiveness of Structured Teaching Programmme Regarding Knowledge on Prevention of Bed Sores among Bsc Nursing 1st Year Students of Army College of Nursing, Jalandhar Cant (International Journal of Nursing Care, 2020)
Decubitus ulcer commonly known as Bed sore or Pressure ulcer is one of the commonest cause of skin andtissue disruptions 1. So here arises a need to create awareness regarding prevention of bed sores througheducation of student nurses to reduce the burden of bed sores. The study was undertaken to assess theknowledge regarding prevention of bed sores among B.Sc Nursing 1st year students and develop andimplement a structured teaching programme in Army College of Nursing, Jalandhar cantt.The objectives of the study were to assess the pre – test knowledge scores, develop and implement structuredteaching programme, to assess the post-test knowledge scores and to compare the pre – test and post- testknowledge scores. The pre experimental study was conducted on 40 selected subjects of B.Sc Nursing 1styear students, Army College of Nursing, Jalandhar cantt, Punjab.Data was collected by self structured questionnaire. The results indicated that the overall pre – test mean was18.32 with the Standard deviation of 2.09 whereas the overall post –test mean knowledge score was 21.42with the Standard deviation of 1.62 with the significant mean diffence of 3.1. Effectiveness of structuredteaching programme was determined by Paired- t test. Value of t was found to be 5.58 which was greaterthan value of t0.05 at 39 degree of freedom that is 2.023.
Keywords: : Bed Sore , Prevention, Knowledge, Structured Teaching Programme.